Foreign Policy of Nepal: Knowledge of Member of House of Representatives 2023 – 2025 AD - Kunwar, Kalidas (Khwopa Journal, 2025)
The research article focused on the critical intersection of legislative awareness based on knowledge of Nepal's foreign policy. Nepal navigates a complex geopolitical milieu; the comprehension and involvement of its representatives in foreign policy are essential. This research explores and analyzes the knowledge of the international relations committee members within the House of Representatives, Government of Nepal, aiming to enhance their contributions to the formulation and implementation of Nepal’s foreign policy during this crucial period. By analyzing the influence of elected political party’s representatives on foreign policy of Nepal and its strategies, the research study underscores the importance of informed decision-making that aligns with both national interests and global trends. Utilizing quantitative research method, the researcher gathers primary data through purposive sampling, which is then, analyzed using SPSS software. The objective is to gain insights into Nepal’s foreign policy standing in the international arena guided by pragmatic research philosophy and employs an inductive approach. It utilizes a quantitative method, specifically through a survey research strategy. The primary data serves as the key source for data collection, with the analysis of quantitative data conducted using SPSS. Finally, the relevance and outcome of the research seems to be a deficiency in political insight among some respondents, as they do not fully grasp the complexities involved in the implementation and political aspects of foreign policy of Nepal in international politics